292 Patient Experience of Urodynamics Within a Urology Unit at a District General Hospital. (19th August 2022) - Hayes, J; Bahn-Christensen, L; Perkins, J; Pullar, B; Foley, C
Abstract: Aim: Urodynamic assessment is an invasive outpatient diagnostic modality that is performed in most urological centres. What is the patient experience of our service, in regard to levels of anxiety, embarrassment and overall satisfaction? Method: Patients undergoing urodynamic investigation, between August and November 2021, were asked to complete a questionnaire, with a visual analogue scale (VAS), where 1 was 'not at all', 2 'a little', 3 'moderate', 4 'a lot' and 5 'extremely'. Levels of anxiety (pre- and peri-procedure), embarrassment, pain and overall satisfaction were assessed. Basic patient demographic data were obtained, in addition to the type of lower urinary tract symptoms (LUTS) under investigation. Results: Questionnaires from 26 patients were obtained. The majority were male (80.8%) with a myriad of symptoms: 30.8% storage, 23% voiding and 46.2% mixed LUTS. The mean overall satisfaction, via the VAS, was 4.35. Anxiety was 3.38 pre-procedure, and 2.23 peri-procedure. Both pain and embarrassment scores were 1.81 and 2.08 respectively. All patients received a urodynamics information leaflet prior to their appointment. Furthermore, all patients would have been willing to undergo the procedure again in the future, if necessary, and recommended the unit to a friend or colleague. Conclusions: On review of our local urodynamics service overall patient satisfaction is excellent, with low levels of peri-procedural anxiety, pain and embarrassment. Prior to their appointment, patients are understandably anxious and additional adjuncts to mitigate this, such as an informative telephone call in advance or urodynamics information video, are currently being explored.